2013
DOI: 10.1371/journal.pone.0078089
|View full text |Cite
|
Sign up to set email alerts
|

Individual Differences in Brain Structure and Resting Brain Function Underlie Cognitive Styles: Evidence from the Embedded Figures Test

Abstract: Cognitive styles can be characterized as individual differences in the way people perceive, think, solve problems, learn, and relate to others. Field dependence/independence (FDI) is an important and widely studied dimension of cognitive styles. Although functional imaging studies have investigated the brain activation of FDI cognitive styles, the combined structural and functional correlates with individual differences in a large sample have never been investigated. In the present study, we investigated the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 91 publications
3
13
0
2
Order By: Relevance
“…This may also be the case for individuals with higher scores in the non-clinical portion of the distribution of autistic traits. In a recent neuroimaging study, Hao et al ( 2013 ) isolated specific anatomo-functional correlates of individual differences in performance at the Embedded Figure Test (a task of visual field independence and piecemeal attention; Shah and Frith, 1983 ) after controlling for the effects of fluid intelligence, as measured with the Raven’s Progressive matrices, age and sex. Overall, this suggests that whilst classical intelligence tests may tap on multiple cognitive components, some of which are relevant for attention to detail, the latter rests on a more restricted set of skills some of which are more basic and encapsulated than general intelligence measures.…”
Section: Discussionmentioning
confidence: 99%
“…This may also be the case for individuals with higher scores in the non-clinical portion of the distribution of autistic traits. In a recent neuroimaging study, Hao et al ( 2013 ) isolated specific anatomo-functional correlates of individual differences in performance at the Embedded Figure Test (a task of visual field independence and piecemeal attention; Shah and Frith, 1983 ) after controlling for the effects of fluid intelligence, as measured with the Raven’s Progressive matrices, age and sex. Overall, this suggests that whilst classical intelligence tests may tap on multiple cognitive components, some of which are relevant for attention to detail, the latter rests on a more restricted set of skills some of which are more basic and encapsulated than general intelligence measures.…”
Section: Discussionmentioning
confidence: 99%
“…Resting state fMRI (rsfMRI) data were acquired using a T2∗-weighted echo-planar imaging sequence [time repetition (TR) = 2000 ms; time echo (TE) = 30 ms; flip angle = 90 ∘ ; field of view (FOV) = 220 mm; Matrix = 64 × 64, 32 slices; 3 mm slice thickness; voxel size = 3.4 mm × 3.4 mm × 3 mm]. For each participant 242 contiguous EPI functional volumes were collected during one run of 8 min and 4 s. Participants were instructed to lie in the scanner with eyes closed while thinking of nothing, and remaining still, relaxed, and awake throughout the scanning session ( Hao et al, 2013 ). Additionally, high-resolution T1-weighted spin-echo images were collected (TR/TE = 1900 ms/2.52 ms; flip angle = 9 ∘ ; FOV = 256 mm; Matrix = 256 × 256; 1 mm slice thickness, 176 slices; voxel size = 1 mm × 1 mm × 1mm).…”
Section: Methodsmentioning
confidence: 99%
“…Since the amplitudes of resting BOLD fluctuations have previously been shown to predict task-evoked BOLD activation as well as relate to cognitive performance (Feng, Feng, & Chen, 2013; Hao et al, 2013; Mennes et al, 2011; Wang et al, 2013; Wei et al, 2012; Xu et al, 2014), and ReHo has been shown to be elevated in the S1 cortex of acupuncturists (known for having high tactile discrimination ability) (Dong et al, 2013), we hypothesized that the local fALFF and ReHo values in the S1 hand region would likewise relate to sensory performance, here in terms of tactile acuity.…”
Section: Introductionmentioning
confidence: 99%